PELATIHAN PENINGKATAN BAHASA INGGRIS GUIDE UNTUK PEMUDA DESA BONDER KECAMATAN PRAYA BARAT LOMBOK TENGAH - Herman; danul1986 (Jurnal WIDYA LAKSMI (Jurnal Pengabdian Kepada Masyarakat), 2022)
AbstractThis community service activity aims to improve English communication skills for tour guides in Bonder Village, West Praya District, Central Lombok Regency. In carrying out this community service activity, the service team uses the interview method and provides questionnaires related to the problems and constraints of the tour guides in communicating using English. The implementation of the service is carried out by giving a pre-test by observing the tour guides in carrying out their duties to accompany and explain the objects of each tourist village to the trainer. From this activity, the tour guides have high motivation to take part in these activities so that training can provide benefits in an effort to improve the English language skills of local guides, so that it is hoped that service to guests who visit tourist areas in Bonder village, Praya Barat District, Central Lombok, in particular can be given optimally, especially foreign guests who come